The Role of Criminology in Combating Law Violations Committed to Fulfilling the Needs of Life - Diah Ratu Sari Harahap (Britain International for Academic Research (BIAR-Publisher), 2022)
The economic conditions of the people are different. Groups of people classified as economically poor, such as beggars, buskers, street vendors, and hawkers, are sometimes forced to violate the law to meet their daily needs. Their activities are considered a disturbance to public order. They were criminalized and threatened with punishment. Earning a living is a human right guaranteed in the 1945 Constitution of the Republic of Indonesia. This situation is a confusion of thought and an error in implementing a worrying state administration. Criminology must play a role in overcoming this problem. The problem proposed in this research is what encourages citizens to violate the law in fulfilling their needs. Do citizens who violate the law in fulfilling their daily necessities need to be punished with criminal charges? What is the role of criminology in tackling this problem? The research method used in this research is a descriptive analysis aimed at describing social phenomena and social realities that occur in such a way so that these conditions can be understood as research in which relevance is achieved. The study results indicate that the factors that encourage community members to violate the law in fulfilling their daily needs are poor economic conditions. People who violate the law in fulfilling their daily needs as long as they are considered disturbing public order do not need to be threatened with criminal charges. Criminology plays a role in finding the causes of law violations committed by citizens in meeting their needs. Through the research results carried out, efforts can be made to overcome them.